Peptide Hydrogels – Versatile Matrices for 3D Cell Culture in Cancer Medicine - Worthington, Peter; Pochan, Darrin J.; Langhans, Sigrid A. (Frontiers in Oncology, 2015)
Traditional two-dimensional (2D) cell culture systems have contributed tremendously to our understanding of cancer biology but have significant limitations in mimicking in vivo conditions such as the tumor microenvironment. In vitro, three-dimensional (3D) cell culture models represent a more accurate, intermediate platform between simplified 2D culture models and complex and expensive in vivo models. 3D in vitro models can overcome 2D in vitro limitations caused by the oversupply of nutrients, and unphysiological cell-cell and cell-material interactions, and allow for dynamic interactions between cells, stroma, and extracellular matrix. In addition, 3D cultures allow for the development of concentration gradients, including oxygen, metabolites and growth factors, with chemical gradients playing an integral role in many cellular functions ranging from development to signaling in normal epithelia and cancer environments in vivo. Currently, the most common matrices used for 3D culture are biologically derived materials such as matrigel and collagen. However, in recent years, more defined, synthetic materials have become available as scaffolds for 3D culture with the advantage of forming well-defined, designed, tunable materials to control matrix charge, stiffness, porosity, nanostructure, degradability and adhesion properties, in addition to other material and biological properties. One important area of synthetic materials currently available for 3D cell culture are short sequence, self-assembling peptide hydrogels. In addition to the review of recent work towards the control of material, structure, and mechanical properties, we will also discuss the biochemical functionalization of peptide hydrogels and how this functionalization, coupled with desired hydrogel material characteristics, affects tumor cell behavior in 3D culture.